MiRNA-513a-5p inhibits progesterone receptor expression and constitutes a risk factor for breast cancer: the hOrmone and Diet in the ETiology of breast cancer prospective study. (4th November 2017) - Muti, Paola; Donzelli, Sara; Sacconi, Andrea; Hossain, Ahmed; Ganci, Federica; Frixa, Tania; Sieri, Sabina; Krogh, Vittorio; Berrino, Franco; Biagioni, Francesca; Strano, Sabrina; Beyene, Joseph; et al.
Abstract : MicroRNAs are regulators of gene expression implicated in cancer development. Using a prospective study, we addressed the possibility that microRNAs serve as biomarkers of breast cancer development. The study observed that upregulation of miRNA-513a-5p was associated with breast cancer risk. Abstract: MicroRNAs (miRNAs) might be considered both predictors and players of cancer development. The aim of the present report was to investigate whether many years before the diagnosis of breast cancer miRNA expression is already disregulated. In order to test this hypothesis, we compared miRNAs extracted from leukocytes in healthy women who later developed breast cancer and in women who remain healthy during the whole 15-year follow-up time. Accordantly, we used a case–control study design nested in the hOrmone and Diet in the ETiology of breast cancer (ORDET) prospective cohort study addressing the possibility that miRNAs can serve as both early biomarkers and components of the hormonal etiological pathways leading to breast cancer development in premenopausal women. We compared leukocyte miRNA profiles of 191 incident premenopausal breast cancer cases and profiles of 191 women who remained healthy over a follow-up period of 20 years. The analysis identified 20 differentially expressed miRNAs in women candidate to develop breast cancer versus control women. The upregulated miRNAs, miR-513-a-5p, miR-513b-5p and miR-513c-5p were among the most significantly deregulated miRNAs. In multivariate analysis, miR-513a-5p upregulation was directly and statistically significant associated with breast cancer risk (OR = 1.69; 95% CI 1.08–2.64; P = 0.0293). In addition, the upregulation of miR-513-a-5p displayed the strongest direct association with serum progesterone and testosterone levels. The experimental data corroborated the inhibitory function of miR-513a-5p on progesterone receptor expression confirming that progesterone receptor is a target of miR-513a-5p. The identification of upregulated miR-513a-5p with its oncogenic potential further validates the use of miRNAs as long-term biomarker of breast cancer risk.